2019
DOI: 10.1177/1350507619849604
|View full text |Cite
|
Sign up to set email alerts
|

Applied tensional analysis: Engaging practitioners and the constitutive shift

Abstract: This article introduces applied tensional analysis as a methodological framework that integrates constitutive ontologies (that depict organizations as processes in constant states of emerging or becoming) with the applied need for practitioners to understand and navigate the everyday exigencies of their organizational experiences. Applied tensional analysis centers analysis on tensions as the key to understanding organizational becoming in contrast to approaches that assume organizations are stable entities an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(42 citation statements)
references
References 33 publications
(98 reference statements)
0
41
0
Order By: Relevance
“…Although the concept of tension as opportunity has existed for some time (see Poole & Van de Ven, 1989), recent research has highlighted this view. For example, Mease (2019) suggested that tensions represent turning points. Specifically, tensions represent critical moments in which organizations are in flux and “organizational actors make choices that ultimately have constitutive implications for the organization” (Mease, 2019, p. 416).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the concept of tension as opportunity has existed for some time (see Poole & Van de Ven, 1989), recent research has highlighted this view. For example, Mease (2019) suggested that tensions represent turning points. Specifically, tensions represent critical moments in which organizations are in flux and “organizational actors make choices that ultimately have constitutive implications for the organization” (Mease, 2019, p. 416).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, Mease (2019) suggested that tensions represent turning points. Specifically, tensions represent critical moments in which organizations are in flux and “organizational actors make choices that ultimately have constitutive implications for the organization” (Mease, 2019, p. 416). This view suggests tensions are not merely stressful circumstances that organizational actors must navigate, but decision points that may give rise to a new organization or alter an existing organization in a fundamental way.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…A recognition of ontological multiplicity also offers a theory of change. It paints a picture of assemblages’ radical indeterminacy, one in which the assemblages constituted by flows of communication make them “ precariously open to disruption ” (Mease, 2019: 412, emphasis in original). Radical indeterminacy resonates with the notion of aleatory materialism (Althusser, 1994): contingency and chance in the assemblage’s potential to become something altogether unexpected.…”
Section: Cco: (Re)moving Blindersmentioning
confidence: 99%